Makna Pistis Christou (Iman/Kesetiaan Kristus) Berdasarkan Roma 3:22 dan 26: Studi Leksikal dan Gramatikal Genitif Subjektif - Renaldi Daniel Malingkas; Robinson Rimun (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
This article examines the meaning of the phrase pistis Christou in Romans 3:22 and 26 through lexical, grammatical, and hermeneutical analysis to determine whether the genitive construction refers to human faith in Christ (objective genitive) or Christ’s faithfulness to God (subjective genitive). Employing a qualitative library research method, the study applies exegetical steps including historical, literary, and theological contextual analysis; syntactical examination of Koine Greek; and semantic investigation of pistis in the Septuagint and Pauline writings. The findings indicate that the semantic field of pistis is best understood as “faithfulness” or “allegiance” rather than merely cognitive belief, and syntactically, the genitive pistis Christou favors a subjective reading. Within Paul’s theological framework, this interpretation emphasizes that justification is grounded not in human faith but in Christ’s faithfulness and obedience to the Father, culminating in His death on the cross. This conclusion shifts the soteriological focus from an anthropocentric to a Christocentric paradigm, consistent with Romans 5:19, which affirms that through the obedience of one man, many will be made righteous. Thus, salvation is presented as God’s act of grace, actualized through Christ’s faithfulness, while human faith functions as a participatory response to Christ's completed redemptive work.